Levamisole-Adulterated Cocaine Induced Skin Necrosis of Nose, Ears, and Extremities: Case Report. Issue 3 (September 2014) - Lawrence, Lauren A.; Jiron, Jose L.; Lin, Ho-Sheng; Folbe, Adam J.
Levamisole is an immunomodulatory and antihelminthic drug, previously removed from the United States market, and now estimated to be present in the vast majority of cocaine distributed in the United States. Levamisole-adulterated cocaine (LAC) exposure can result in neutropenia, thrombocytopenia, and vasculitis with a predilection for subsites of the face. The objective of this review is to increase awareness among otolaryngologists of the manifestations of LAC exposure. We present the case of a 33-year-old woman with a history of cocaine use, consulted for purpuric, necrotic lesions of the nose, cheeks, and ears, with accompanying leukopenia, thrombocytopenia, and positive antineutrophil cytoplasmic antibodies (ANCA). The effects of levamisole are immune mediated, with antibodies directed against neutrophils causing neutropenia, and vasculitis caused by antibody deposition or secondary to induction of antiphospholipid antibodies causing thrombosis. LAC exposure can be differentiated from other similar appearing pathologies by evaluating serology for specific ANCA. The most important treatment is cessation of cocaine use, which most often results in complete resolution of symptoms. Awareness of the presentation, complications, and treatment of LAC exposure may be especially important for otolaryngologists, who may be one of the firsts to evaluate an affected patient.